The good, the bad, and the talented: Entrepreneurial talent and other-regarding behavior - Utz Weitzel; Diemo Urbig; Sameeksha Desai; Zoltán J. Ács; Mark Sanders (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2009)
Talent allocation models assume that entrepreneurial talent is selfish and thus allocates into unproductive or even destructive activities if these offer the highest private returns. This paper experimentally analyzes other-regarding preferences of entrepreneurial talent. We find that making a distinction between creative talent and business talent explains systematic differences in other-regarding behavior. Generally, business talent is less willing, and creative talent more willing, to forego private payoffs to avoid losses to others. A moderator analysis reveals that uncreative business talent is significantly less other-regarding than creative business talent, a finding applicable to both certain and risky payoffs with and without negative externalities. The paper makes a contribution to entrepreneurship research by qualifying the implications of talent allocation models and discovering the importance of distinguishing between the two types of entrepreneurial talent. We also add to the field of experimental economics by advancing research on social preferences under risk and with negative externalities.
Keywords: C91; D62; D64; L26; 330; Social preference; entrepreneurship; experiment; Unternehmer; Kreativität; Soziales Verhalten; Soziale Wohlfahrtsfunktion; Test